High-molecular weight cellulose ether influence on the adhesive properties of fresh mortars - Hai, Le Thanh; Tien, Phan Van (Vietnam Journal of Science and Technology, 2015)
This paper presents an experimental study on the effect of three types of high molecular weight cellulose ethers (HEMCs) on the adhesive properties of cement mortars in fresh state. To determine the adhesive properties the probe tack test was used. The tack test results have been exploited to identify the adhesion strength, the cohesion strength and the support’ adherence force. The results indicate an important role of the molecular weight of cellulose ether on the adhesion force, the cohesion force of mortars in fresh state. Therefore, the molecular weight is a crucial parameter in controlling the adhesive properties of fresh mortars. However, it does not affect the adherence force. An optimum value regarding the interface adherence has been observed, indicates that there is an optimum dosage of HEMCs when dealing with interface adherence of mortars.